A systematic review of cellular immunological variations in response to anesthesia in healthy dogs - Alzate, Ana María (2020)
The aim of this review was to systematically explore the scientific evidence of the immunological changes associated with anesthesia in clinically healthy canines, whether or not they underwent surgical procedures, in order to provide information of interest about tools, protocols and processes that allow patients to veterinary anesthesiologists take an additional point of view in patient care. From the PRISMA methodology, an initial search process was carried out on the OVID®, SciELO Citation Index® and Redalyc® search platforms. Based on a research question, a search for relevant titles was carried out, considering only original articles and case reports published in indexed journals and under peer review processes. Subsequently, the reference lists of the definitive articles were searched for additional information (snowballing). Four articles were considered for the presentation of final results and discussion, all published in English, between 2002 and 2015. From the information collected from the four studies, it can be inferred that there are immunological variations in patients undergoing general anesthesia, finding differences in immune responses between total intravenous and inhaled anesthesia. Additionally, it is noteworthy the absence of experimental research that allows not only to analyze the differences between the types of anesthesia, but also between the different anesthetic protocols and patients with concomitant diseases.